Nothing-on-road bridge weigh-in-motion considering the transverse position of the vehicle. Issue 8 (3rd August 2018) - Yu, Yang; Cai, C.S.; Deng, Lu
Abstract: Bridge weigh-in-motion (BWIM) is a technology that uses the bridge as a weighing platform to estimate vehicle weights. Previous research has shown that ignoring the transverse position (TP) of vehicles may lead to significant identification errors of vehicle weight for BWIM systems. However, the traditional method to identify the vehicle's exact TP requires using axle detectors on the road surface. Aiming at achieving the nothing-on-road (NOR) BWIM, this paper proposes a novel NOR BWIM algorithm that is able to identify the vehicle's TP and axle weights using only the weighing sensors. Numerical simulations are conducted using three-dimensional vehicle and bridge models and the proposed algorithm was used to identify the vehicle's TP and axle weights. The results show that the proposed algorithm can successfully identify the vehicle's TP and that the identification accuracy of axle weights and gross vehicle weight is significantly improved after considering the vehicle's TP. The effects of the road surface condition, the vehicle speed, the vehicle width, and different measurement stations on the identification accuracy are investigated. The proposed algorithm is then verified by a field study and the results indicate that the proposed algorithm can achieve acceptable identification accuracy in practice.